Resistance to Racial Equity in U.S. Federalism and Its Impact on Fragmented Regions. Issue 6 (August 2020) - Grigsby, Sheila; Hernàndez, Alicia; John, Sara; Jones-Smith, Désirée; Kaufmann, Katie; Patrick, Cordaryl; Prener, Christopher; Tranel, Mark; Udani, Adriano
In this commentary, we provide our ground-level observations of how the novel coronavirus disease (COVID-19 or COVID) has exposed weaknesses in our federal system to respond to local communities, particularly Black and Latina/os who live and work in the St. Louis region. Our perspectives come from a virtual town hall hosted by the Community Innovation and Action Center (CIAC) at the University of Missouri, St. Louis on April 18, 2020. Based on these initial public discussions, we use St. Louis as a lens for arguing that government's attenuated impact is not due to a natural disaster itself, but the inevitable result of race-based policies that had worked against Black peoples over generations. The real failure involves our federalist system's lack of a commitment to racial equity—when race no longer is used to predict life outcomes, and outcomes for all groups are improved—when designing the federal plan to respond to COVID-19 in local communities.